O estilo Gonzo como catalisador de fronteiras – jornalismo e literatura: comparando Hunther Thompson e Xico Sá - Rodrigues, Ligia Coeli Silva (2012)
The objective of this research was compare the use of the Gonzo style in the journalists Hunter S. Thompson and Xico Sá. To check the extent to which they use this style as a way to avoid censorship and write critically and unusual, in hybrid form, unveiling details in texts that could not be shown with other resources. For this, observe the circumstances under which Thompson takes this new journalistic style and produces a literary work. Comparing the writers-journalists, as noted Gonzo is successfully applied to both journalistic texts as for literature. Our theoretical basis using comparative and critical journalistic critics, including Thompson himself as the creator of this style. The choice of comparative criticism was motivated with the aim of bringing these writings without reducing them to action to establish social hierarchies, or intellectual power to reach readers, but starting to look a style of his creation (Thompson) up to a likely manifestation (Xico Sá). We realized that the work of Sá is no mere stylistic copy, but it illustrates a way of writing that presents similarities to Gonzo when breaking paradigms in Brazilian journalistic context and brings to light the way of writing that goes beyond barriers in time and is present in contemporary. The 'influence', seen from the perspective of comparative theory, does not reduce the value writer influenced. The comparison allowed us to highlight the features of Gonzo more clearly in both works and thus we conclude that the use of this style is not limited to journalism, can be used in literary works, without compromising their specific characteristics.